Implementing a Clinician-Built High-Dose Antipsychotic Therapy (HDAT) Calculator and Tracker: A Quality Improvement Project to Optimise HDAT Monitoring and Safe Prescribing - Nurul Ain Mohd Nizam; Isabelle Tighe; Claire Butler; Paul Harris (BJPsych Open)
Aims: High-dose antipsychotic therapy (HDAT) carries an increased risk of adverse effects, including metabolic syndrome and extrapyramidal side effects, requiring regular monitoring. However, adherence remains inconsistent due to challenges in patient attendance, staff awareness, and varying monitoring intervals. This quality improvement project aimed to determine the prevalence of HDAT use in an assertive outreach team, assess adherence to the local trust HDAT monitoring guidelines, and implement a clinician-built HDAT Calculator and Tracker to improve monitoring efficiency.